Diversity of Trees in Hin Chang Si, Nam Phong National Park, Nong Ruea District, Khon Kaen Province - กระจาย, พันธ์ทิวา; สายศร, วิษณุ; จันทรโณทัย, ประนอม; ดีปราสัย, วรพล; พรพงศ์รุ่งเรือง, พิมพ์วดี (KKU Science Journal, 2013)
A survey and taxonomic investigation of tree species along the nature trail at Hin Chang Si, Nam Phong National Park, Nong Ruea district, Khon Kaen province was carried out between January 2010 and December 2011. Seventy seven species, 61 genera and 33 families were enumerated. Due to lack of flowering or fruiting materials, which are the most important part for species identification, five specimens and two specimens can only be identified at generic and familial levels, respectively. The largest family is Leguminosae, with 13 genera and 15 species. The second largest family is Euphorbiaceae, with six genera and eight species.